2012
DOI: 10.1371/journal.pone.0043284
|View full text |Cite
|
Sign up to set email alerts
|

Validating Serum S100B and Neuron-Specific Enolase as Biomarkers for the Human Brain – A Combined Serum, Gene Expression and MRI Study

Abstract: IntroductionFormer studies have investigated the potential of serum biomarkers for diseases affecting the human brain. In particular the glial protein S100B, a neuro- and gliotrophin inducing plasticity, seems to be involved in the pathogenesis and treatment of psychiatric diseases such as major depression and schizophrenia. Neuron-specific enolase (NSE) is a specific serum marker for neuronal damage. However, the specificity of these biomarkers for cell type and brain region has not been investigated in vivo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
67
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(81 citation statements)
references
References 73 publications
13
67
0
Order By: Relevance
“…The finding of positive correlation between S100B and white matter hyperintensities in healthy subjects is in agreement with a study by Streitbuerger et al (2012). These authors reported an association between serum S100B and the diffusion tensor imaging parameters fractional anisotropy and radial diffusivity in white matter tracts in healthy females.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The finding of positive correlation between S100B and white matter hyperintensities in healthy subjects is in agreement with a study by Streitbuerger et al (2012). These authors reported an association between serum S100B and the diffusion tensor imaging parameters fractional anisotropy and radial diffusivity in white matter tracts in healthy females.…”
Section: Discussionsupporting
confidence: 92%
“…The differences between our and the former study might be attributed to the differences in the studied samples with regard to disease severity and age. Further studies are in agreement with our finding for healthy subjects by showing higher S100B in healthy female than male adults (Streitbuerger et al, 2012) and children (Gazzolo et al, 2003). Overall, the literature on effects of gender on S100B did not reach consensus so far.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Emerging studies have demonstrated that necrosis and apoptosis of brain neurons occur while brain damage is taking place. Neuron-specific enolase (NSE) and S100B have been confirmed to be specific markers of brain damage (3). B7 homolog 3 (B7-H3) is a newly identified member of the B7 superfamily, which serves a key function in the regulation of immune responses (4).…”
Section: Introductionmentioning
confidence: 99%
“…Most of it is distributed in the CNS and makes up 1.5 % of soluble protein in the brain [3]. NSE concentrates exclusively in the cytoplasm of neurons and may serve as a marker of neuronal damage [4].…”
mentioning
confidence: 99%